Pengaruh Promosi Terhadap Keputusan Pembelian Konsumen Pada Majestyk Bakery & Cake Shop Cabang Katamso - Ronnie Togar Mulia Sirait; Maretta Ginting; Eva Solita Pasaribu (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2023)
This research aims to determine and analyze the influence of promotions on consumer purchasing decisions at Majestyk Bakery & Cake Shop Katamso Branch. The research method used is quantitative descriptive. The population in this study were consumers of Majestyk Bakery & Cake Shop, Captain Muslim Medan Branch. The technique for determining the sample in this study used purposive sampling with reference to the Lameshow formula approach, obtaining 96 respondents. Data analysis used simple linear analysis. The research results obtained are that promotion has a positive and significant effect on consumer purchasing decisions at Majestyk Bakery & Cake Shop Katamso Branch.